Coronary artery changes in congenital coronary-cameral fistulas evaluated by computed tomographic angiography - Suvipaporn Siripornpitak (2022)
Purpose: The study sought to determine coronary artery diameter in congenital coronary-cameral fistula (cCCF), factors associated with coronary artery aneurysm, coronary artery changes after fistula closure, and computed tomographic (CT) findings after treatment. Materials and methods: We retrospectively reviewed CT findings of the cCCF for origins, terminations, fistula length, complexities, and Sakakibara classification. Coronary artery diameter was expressed as coronary artery Z score. Fistula features associated with coronary artery aneurysm were analyzed. Post-fistula closures were analyzed for coronary artery dilatation, coronary thrombosis, complete fistula closure, and fistula thrombosis. Results: Twenty-five patients (median age 33 months, interquartile range, IQR 25–48) were included. Coronary feeders and terminations were frequently right coronary artery (48%) and right ventricle (56%), respectively. Fistula aneurysm occurred in 52% of cases. Mean coronary artery Z score was 13.03 ± 6.36 with a high incidence of giant coronary artery aneurysm (68%). We found no statistically significant risk factors associated with coronary artery aneurysm (p value range 0.075–0.370). Median duration of the follow-up CT after closure of the fistulas was 6.4 months (IQR 5.0–8.7). Coronary artery Z score significantly decreased by 0.82 (IQR 0.28–1.35), p = 0.006 and coronary thrombosis occurred in 23% of cases during follow-up. Conclusions: Large coronary aneurysm is common in cCCF. No characteristic feature of the fistula influencing coronary artery aneurysm is identified. There is a diminution in coronary artery Z score after fistula closure. Coronary thrombosis is a major complication after treatment.